The Effect of the Cooperative Learning Model of the Numbered Heads Together Type Assisted by Question Cards on the Social Studies Learning Outcomes of Students at SMPN 17 Surabaya - Monica Fiantia; Dian Ayu Larasati; Nuansa Bayu Segara; Dhimas Bagus Virgiawan (Jurnal Dialektika Pendidikan IPS, 2026)
The Numbered Heads Together (NHT) cooperative learning model is a group-based instructional strategy that promotes students’ activeness, collaboration, and individual responsibility in discussions, thereby improving learning outcomes. This study aims to analyze the effect of the Numbered Heads Together (NHT) cooperative learning model assisted by question cards on the social studies learning outcomes of eighth-grade students at SMPN 17 Surabaya on the topic of Indonesian Social Diversity. The research problem was based on the low level of student participation and learning achievement in social studies. This study employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group design. The research subjects consisted of 60 students, divided into 30 students in the experimental class and 30 students in the control class. Data were collected through an essay test based on Higher Order Thinking Skills (HOTS), which had been tested for validity and reliability (Cronbach’s Alpha = 0.949). Data analysis was conducted using the Wilcoxon test to determine differences within groups and the Mann–Whitney test to examine differences between groups. The results showed that the average posttest score of the experimental class (84.77) was higher than that of the control class (68.20). The Mann–Whitney test indicated a significance value of 0.000 (<0.05), demonstrating a significant difference in learning outcomes between the two groups. The effect size value of 0.86 indicated a strong effect. Therefore, the NHT cooperative learning model assisted by question cards is more effective than conventional learning in improving students’ social studies learning outcomes.